Formation of methodology of decision-making on a choice of strategy of development of the monogrocery region within cluster approach - V. Y. Avtonova; O. V. Astafeva (Путеводитель предпринимателя)
Methodological approach is presented in article to adoption of the reasonable decision on a choice of the strategic direction ofdevelopment of the monogrocery region, consisting of two stages - the qualitative and quantitative analysis, and theoretical regulations on carrying out a quantitative assessment of expediency of creation ofan innovative cluster on the basis of usefulness model are developed.